Parameter tuning of model predictive controller: a case study - Askari, M.; Mohamed, H.A.F.; Moghavvemi, M.; Yang, S.S. (2009)
This paper presents parameter tuning of model predictive controller. The effect of prediction horizon on the stability of the system is studied. The performances of model predictive controller and linear quadratic regulator on the inverted pendulum are compared.